"Sí, se puede": a busca pelo diploma superior em medicina na fronteira Br-Py - Webber, Maria Aparecida (2023)
This thesis seeks to understand transnational urban displacements motivated by the opportunity to access medical training in the border context between Brazil and Paraguay. In the last decade, the growing supply of places to study Medicine in Paraguayan Private Higher Education Institutions has met a demand from Brazilian men and women who seek conditions to become doctors but encounter limitations in the regulation of this supply in Brazil. The national border demarcated by the Paraná River, which separates the cities of Foz do Iguaçu (BR) and Ciudad del Este (PY) is not perceived or experienced as a limit by these students, as it is, first and foremost, the possibility of obtaining the diploma of a doctor. My argument is that this higherlevel student mobility is driven by the interdependence of the objective conditions of medical training between these two countries, at the same time that it establishes experiences that go beyond the notion of border as a limit for these students. Even though it is supposed to be necessary, the border is experienced by them as diluted and relativized. The border is approached as being inscribed in the lives of these students who, in search of medical training, cross border legal controls and national corporatist regulations, instituting specific ways of experiencing it. To understand this mobility, I address the forces of emigration, the migratory phenomenon, highlight the border rearrangements that involve the stay of these students and present the expectations of return to enter the job market in Brazil. The ethnographic fieldwork followed the experiences and life stories of these medical students in person, between the daily comings and goings at Ponte da Amizade, in university spaces, as well as in the virtual environments of interactions experienced by them through networks social media, messaging apps, websites and blogs. I also followed the publication of news in newspapers and related profiles, as well as addressing the main legislation, policies and programs linked to medical training in Brazil and Paraguay. The different dimensions of the border are arranged as an articulating axis for the research and lives of these students who, in pursuit of their dream of becoming doctors, cross cultural, legal and legal configurations between these countries.